Recent Progress in Amorphous Carbon‐Based Materials for Anodes of Sodium‐Ion Batteries: Synthesis Strategies, Mechanisms, and Performance. Issue 18 (5th August 2021) - Sarkar, Samrat; Roy, Swagata; Hou, Yanglong; Sun, Shuhui; Zhang, Jiujun; Zhao, Yufeng
Abstract: Sodium‐ion batteries (SIBs) are gaining renewed interest as a promising alternative to the already commercialized lithium‐ion batteries. The large abundance, low cost, and similar electrochemistry of sodium (compared with lithium) is attracting the attention of the research community for their deployment in energy storage devices. Despite the fact that there are adequate cathode materials, the choice of suitable anodes for SIBs is limited. Graphite, the most versatile anode for LIBs, exhibits poor performance in case of SIBs. Amorphous or disordered carbons (hard and soft carbon) have been the most promising and cost‐effective anode materials for SIBs. This Review discusses the recent advances of various forms of amorphous or disordered carbons used in SIBs with emphasis on their synthesis processes and relationship between microstructure, morphology, and performance. A profound understanding of the charge storage mechanisms of sodium in these carbon materials has been deliberated. The performance of these anode materials also depends upon electrolyte optimization, which has been aptly conferred. However, these anodes are often plagued with large voltage loss, low initial coulombic efficiency, and formation of solid electrolyte interphase. In order to overcome these challenges, several mitigation strategies have been put forward in a concise way to offer visions for the deployment of these amorphous carbon materials for the progress and commercial success of SIBs. Abstract : Carbon anodes : Application of amorphous carbon materials as anodes of sodium‐ion batteries is highlighted with emphasis on various synthesis strategies and charge storage mechanisms with discussion on their electrochemical performance.